Evaluation of Educational Management in Improving Teacher Competence to Achieve National Elementary School Education Standards - Susanto, Ratnawati; Agustina, Noni; Yulhendri; Nasution, Evi Syafrida (LPPM Undiksha, 2025)
The competency of elementary school teachers does not all meet national standards, thus affecting student learning outcomes and the achievement of national education standards. The urgency of this research is the need for effective and sustainable education management strategies to improve teacher competency comprehensively. This study aims to analyze the framework of adaptive and sustainable education management strategies, analyze the factors that support success, and formulate appropriate policy recommendations. The research method used a quantitative approach with descriptive regression analysis on data from 230 randomly selected teachers in Jakarta. Data collection techniques included questionnaires, interviews, and documentation, then analyzed using descriptive statistics and multiple regression. The study results indicate that effective learning management strategies, transformational leadership support, and resources significantly improve teacher competency. These findings indicate the need to strengthen continuous professional development programs and transparent performance evaluations. It is concluded that comprehensive and adaptive education management strategies can improve teacher competency, support the achievement of national education standards, and improve the quality of education in Indonesia. Suggestions are provided to the government and educational institutions to promote innovation and collaboration in the continuous development of teacher competency.